2016
DOI: 10.1080/02786826.2016.1257853
|View full text |Cite
|
Sign up to set email alerts
|

Transport phenomena governing nicotine emissions from electronic cigarettes: Model formulation and experimental investigation

Abstract: Electronic cigarettes (ECIGs) electrically heat and aerosolize a liquid containing propylene glycol (PG), vegetable glycerin (VG), flavorants, water, and nicotine. ECIG effects and proposed methods to regulate them are controversial. One regulatory focal point involves nicotine emissions. We describe a mathematical model that predicts ECIG nicotine emissions. The model computes the vaporization rate of individual species by numerically solving the unsteady species and energy conservation equations. To validate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
88
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 91 publications
(103 citation statements)
references
References 9 publications
14
88
1
Order By: Relevance
“…AcP represented well the behavior of the pyrazines in the commercial samples since it was the most abundant in the tested liquids. We observed complete evaporation of AcP from the sample holder at 130 °C, which was considered a lower temperature than the reported temperatures in the vicinity of the ECIG heating element (Geiss et al 2016, Talih et al 2017). …”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…AcP represented well the behavior of the pyrazines in the commercial samples since it was the most abundant in the tested liquids. We observed complete evaporation of AcP from the sample holder at 130 °C, which was considered a lower temperature than the reported temperatures in the vicinity of the ECIG heating element (Geiss et al 2016, Talih et al 2017). …”
Section: Discussioncontrasting
confidence: 55%
“…PG and VG were quantified using a previously reported method (Talih et al 2017). In brief, 2 µL of liquid was dissolved in 1 mL of ethyl acetate and sonicated for 30 min.…”
Section: Ecig Liquid Chemical Characterizationmentioning
confidence: 99%
“…In light of results from the present study and other results (Wagener et al, 2017), policies aimed at limiting ECIG nicotine delivery to the user likely will need to account for more factors than liquid nicotine concentration alone: user behavior and device power are also relevant. A mathematical model is available that predicts the rate of ECIG nicotine emissions (e.g., nicotine flux; Shihadeh & Eissenberg, 2015) and it takes into account many factors, including liquid nicotine concentration, user behavior, and device power (Talih et al, 2017). Such models are potentially valuable regulatory tools.…”
Section: Discussionmentioning
confidence: 99%
“…These device components were selected after preliminary testing revealed that their nicotine emissions approached those of a tobacco cigarette under some conditions (see Talih et al, 2015; 2017). The cartomizer was pre-loaded with 1 ml of a flavored liquid (tobacco or menthol; chosen by participants at screening), that was comprised of 70% PG and 30% VG (AVAIL Vapor, Richmond, VA).…”
Section: Methodsmentioning
confidence: 99%
“…With regard to users, higher power devices may increase abuse liability and nicotine dependence as higher power devices produce more nicotine-containing aerosol for inhalation (e.g., Sleiman et al, 2016; Talih et al, 2017) and may also increase adverse health effects as the aerosol produced by these higher power devices also can be more toxicant-laden than low power devices (Gillman et al, 2016; El-Hellani et al, 2016). With regard to policymakers, the availability of higher power devices limits the impact of regulations regarding nicotine liquid concentration.…”
Section: Introductionmentioning
confidence: 99%